Optimised Layout And Roadway Support Planning With Integrated Intelligent Software - S. Kouniali (International Conference on Ground Control in Mining, 1996)
Experience with knowledge-based systems for Layout planning and roadway support dimensioning is on hand in European coal mining since 1985. The systems SOUT (support choice and dimensioning, 1989), SOUT 2, PLANANK (planning of bolt-support), EXOS (layout planning diagnosis. 1994), Sout 3 (1995) have been developed in close cooperation by CdF1. INERIS2. EMN3 (France) and RAG 4, DMT5, TH - Aachen6 (Germany); ISLSP (Integrated Software for Layout and support planning) development is in progress (completion scheduled for July 1996). This new software technology in combination with conventional programming systems. numerical models and existing databases turned out to be suited for setting-up an intelligent decision aid for layout and roadway support planning. The system enhances reliability of planning and optimises the safety-to-cost ratio for ? deformation forecast for roadways in seam and surrounding rocks, consideration of the general position of the roadway in the rock mass (zones of increased pressure, position of operating and mined panels). ? support dimensioning ? yielding arches, rigid arches, porch sets, rigid rings, yielding rings and bolting / shotcreting for drifts ? yielding arches, rigid arches and porch sets for roadways in seam ? bolt support for gateroads (assessment of exclusion criteria and calculation of the bolting pattern) ? bolting of face-end zones (feasibility and safety assessment, stability guarantee).